STRAIN IDENTIFICATION AND EVALUATION OF PCR BASED MOLECULAR METHODS FOR SUBTYPING OF MYCOBACTERIUM TUBERCULOSIS CLINICAL ISOLATES - M. KATHIRVEL; K. VALLAYYACHARI; R. THIRUMURUGAN; B. USHARANI; ANTONY V. SAMROT; M. MUTHURAJ (International Journal of Pharma and Bio Sciences, 2014)
Drug susceptibility profile of 53 Mycobacterium tuberculosis clinical isolates was studied by conventional solid and liquid culture methods. Forty three isolates were drug resistant to at least one drug and 10 were susceptible. The strain identification was performed by PCR amplification of mtp40 gene and strain subtyping was performed by Double Repetitive Element-PCR (DRE-PCR), IS6110 outward primers-PCR and Random Amplified Polymorphic DNA-PCR (RAPD-PCR). Strains were best discriminated by DRE-PCR (15 patterns), followed by RAPD-PCR (11 patterns), and IS6110-PCR (7 patterns). The PCR amplification of mtp40 gene was evaluated for the rapid differentiation of M. tuberculosis and M. bovis. The DRE-PCR method showed highest reliability than the other methods and provided a useful alternative tool for subtyping of M. tuberculosis clinical isolates and thus offers simple procedure to demonstrate that prevalence of TB in Puducherry region.